Gestão executiva feminina: inovações e permanências - Araújo, Ione Maria Santos de (2013)
This research aims to analyze the continuities and innovations in managing female executive in relation to the categories of process of decision making, model of leadership, personal communication and interpersonal skills. With the growth of womens presence in the world of work, women began to increasingly occupy positions high in organizations, leading to a question about the continuities and innovations arising from way of them to manage the executive. Is it possible that the women have new patterns and models of management or follow characteristic patterns of male management? To achieve the proposed objectives we decided to conduct this research with phenomenological inspiration considering the interpretation that each individual who was researched presents from the reality experienced in the management of the organizations to which they belong. This is a qualitative research, using a case study as method, based on women in positions of senior management in companies Sergipe. The data collected were analyzed using the technique of discourse analysis. From the data obtained it can be seen that the executive clearly perceives differences of management between the way of males and the females with respect to categories analyzed. For the interviewed women, for the categories chosen, women have more flexible and humanitarian characteristics, while men are considered more inflexible, objectives and in some cases more austere. It can be concluded that women consider that in their executive management uses innovative features with respect to the categories analyzed. As for permanences of male management characteristics, only a minimum number of respondents pointed to use some nuances of managing men, not as a guide but in order to merge the two modes of management in specific situations.